Technological audit as a method of evaluation of the commercial attractiveness of the objects of intellectual property - Kosenko, Aleksandra (University of Miskolc, 2013)
Considered in this paper are the questions used to assess the commercial potential of intellectual property objects in the theory and practice of the technological audit. A mechanism for the valuation of the level of commercial attractiveness of intellectual technologies is proposed, and the theoretical provisions of principles, objectives, and outcomes of technological audit are discussed. The features of the technological audit of the results of intellectual activities of industrial enterprises are determined.